ISEP/INESC TEC Aerial Robotics Team for Search and Rescue Operations at the EuRathlon Challenge 2015 - Sousa, P. (2016)
This paper presents the autononomous aerial vehicle OTUS and its application to search and rescue scenarios, namely the participation on the EuRathlon 2015 competition. The OTUS robot was developed at INESC TEC/ ISEP for research in cooperative aerial robotics and applications in complex and dynamic environments. The system was validated in this challenging scenario and was able to win the Grand Challenge scenario in